Simple and rapid determination of free fatty acids in brown rice by FTIR spectroscopy in conjunction with a second-derivative treatment. (15th January 2016) - Genkawa, Takuma; Ahamed, Tofael; Noguchi, Ryozo; Takigawa, Tomohiro; Ozaki, Yukihiro
Highlights: A simple and rapid FTIR method for determination of FFAs in brown rice was developed. Toluene can be used for the background spectrum for FTIR measurements. Second-derivative treatment efficiently separated the FFA band from other bands. A single linear regression model showed high prediction accuracy. Abstract: A simple and rapid method for the determination of free fatty acid (FFA) content in brown rice using Fourier transform infrared spectroscopy (FTIR) in conjunction with second-derivative treatment was proposed. Ground brown rice (10 g) was soaked in toluene (20 mL) for 30 min, and the filtrate of the extract was placed in a 1 mm CaF2 liquid cell. The transmittance spectrum of the filtrate was recorded using toluene for the background spectrum. The absorption band due to the CO stretching mode of FFAs was detected at 1710 cm −1, and the Savitzky–Golay second-derivative treatment was performed for band separation. A single linear regression model for FFA was developed using the 1710 cm −1 band in the second-derivative spectra of oleic acid in toluene (0.25–2.50 g L −1 ), and the model displayed high prediction accuracy with a determination coefficient of 0.998 and a root mean square error of 0.03 g L −1 .